The Effect of Corruption on Foreign Direct Investment: A Panel Data Study - EPAPHRA, Manamba; MASSAWE, John (Turkish Economic Review, 2017)
Abstract. Foreign direct investment (FDI) has become an important factor of development in low income countries. At the same time, corruption continues to be one of the greatest obstacles to economic and social development in these countries. However, in East Africa, the study of the nature of corruption as well as its relationship with FDI is scanty in socio-economic literature. In addition, the existing literature provides controversial results. Motivated by these issues, this paper examines the effects of corruption on FDI inflows by incorporating an econometric method based on panel data from 5 East African countries over the 1996-2015 period. The paper contributes to the existing literature by modeling the relationship between corruption and FDI inflows using two measures of corruption, namely corruption perception index (CPI) and control of corruption (CC). Equally important, both economic factors such as GDP per capita, GDP growth, inflation and degree of openness, and quality of institutions or governance indicators such as voice and accountability, political stability and absence of violence, government effectiveness and rule of law are considered in the analysis. Data were obtained from Transparency International, World Bank Development Indicators, Worldwide Governance Indicators and United Nations Conference on Trade and Development. Analytically the paper uses fixed effects (FE) as the preferable model. The results show that the corruption level in the host country has an adverse effect on FDI inflows when eliminating GDP per capita in the regression. Nonetheless, the results show that the GDP per capita as a proxy for market size and country’s quality of institutions are more important than the level of corruption in encouraging FDI inflows into the country. The key implication of these results is that improvement in the quality of institutions and control of corruption may be an important strategy for increase FDI inflows. The key implication of these results is that an increase in the real GDP per capita, improvement in the quality of institutions as well as control of corruption may be an important strategy for increase FDI inflows. Keywords. Corruption, Foreign direct investment, Quality of institutions. JEL. C23, F21, F23, E02, O16.